If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4x+2)=(7x-6)
We move all terms to the left:
(4x+2)-((7x-6))=0
We get rid of parentheses
4x-((7x-6))+2=0
We calculate terms in parentheses: -((7x-6)), so:We get rid of parentheses
(7x-6)
We get rid of parentheses
7x-6
Back to the equation:
-(7x-6)
4x-7x+6+2=0
We add all the numbers together, and all the variables
-3x+8=0
We move all terms containing x to the left, all other terms to the right
-3x=-8
x=-8/-3
x=2+2/3
| 2n^{2}-8n-24=0 | | (2n=4) | | 5^0.1x=10/3 | | 4n−6=10n+7 | | 5x-4=6x=2 | | (3x+6)/2=5/4 | | 2x=√-5x+24-3 | | 24y+3y=21 | | -4(x)=2x2-1 | | y-0.9y=4400 | | k/5+4=2 | | 5x10=10x | | 7+m/2=16 | | (4+0.03y)*(2-y)=8 | | Y=2x;(1/4) | | 14+a/6=4 | | -5-10m=-175 | | n/7-6=-4 | | b/7-9=-6 | | v/2-12=-18 | | n/5=30. | | 6+v/16=9 | | 3/m+10=4/8m+5 | | -2(7x-2)+6=-14x+10 | | v=24640*0.19*0.75 | | 10k-1=239 | | H=6πm | | 10a+2=152 | | 49/7=30-f | | -14+n/6=17 | | 14+x/2=3 | | 225=41/2*x |